A moveable feast – law librarianship in the noughties - Ruth Bird (2006)
The paper will examine what links law librarians, no matter where we work. It will then move on to look at some of the impacts of globalisation that affect us directly, before investigating several issues common to us all. And finally, I will list some challenges that we face wherever we are based..